Transformation Of The Visual Motifs Of The Kamasan Puppets Into Figurative Characters - Devi, Putu Durga Laksmi; Utami, Ni Made Purnami; Sujana, I Wayan (Program Studi Seni Murni ISI Bali, 2024)
This thesis contains a description of the creation of a work of painting with the theme